Greater Occipital Nerve Blockade in Chronic Migraine: Meta-Analysis - Dwiastri Iris Sarwastuti (Al-Hayat: Natural Sciences, Health & Environment Journal, 2025)
Chronic migraine significantly impacts quality of life and remains a therapeutic challenge, with many patients experiencing limited relief from traditional treatments. Greater occipital nerve (GON) blockade has emerged as a potential intervention, utilizing bupivacaine to alleviate migraine frequency and severity. This meta-analysis assesses the efficacy of GON blockade in reducing headache days per month in patients with chronic migraine. A meta-analysis was conducted, encompassing four randomized, placebo-controlled studies published between 2014 and 2024. The studies included a total of 202 participants (105 in the intervention group and 97 in the placebo group) who received GON blockade with bupivacaine or a placebo. The primary outcome measured was the mean difference in monthly headache days between the intervention and placebo groups. Statistical heterogeneity across studies was also assessed. The pooled analysis revealed a statistically significant reduction in monthly headache days in the GON blockade group compared to placebo, with an average difference of -5.7 days (95% CI: -8.5 to -2.9; p < 0.0001). Individual studies demonstrated consistent reductions in headache days in the intervention group, with mean differences ranging from -1.1 to -12.8 days. Heterogeneity was moderate (I² = 30.3%), indicating some variability across studies but an overall trend favoring the intervention. This meta-analysis supports the efficacy of GON blockade with bupivacaine as a promising treatment option for chronic migraine, showing a meaningful reduction in headache frequency. While GON blockade demonstrates short-term benefits, further research with extended follow-up periods and larger, more diverse samples is recommended to evaluate its long-term effectiveness and generalizability. These findings suggest that GON blockade may offer substantial relief for patients suffering from chronic migraines, providing a potential alternative for those who have not responded to conventional therapies.